ETEC DANS: uma escola profissionalizante - Oliveira, Arlete Piccolo de (2020)
This investigation aims to rescue the institutional memory of the State Technical School Doctor Adail Nunes da Silva or ETEC DANS, an autarchy of the State Center for Technological Education Paula Souza, linked to the Secretariat of Economic Development of the State of São Paulo. Created by Law Decree 29.098, of November 3, 1988, with initial nomenclature of Escola Técnica Nova Vila Rosa. The absence of a systematized record gives the research the character of originality, since investigations about school institutions are precarious, valid arguments in the justification of this study. The questions that guided the research can be summarized in the history of the municipality, the historical linearity of ETEC DANS and its relationship with vocational high school, which, unified, resulted in the thesis ETEC DANS a vocational school. The dialectical method of investigation was used and, for this purpose, four points were guiding factors: formal authorization of the institution, bibliographic research, field research in loco both at school and in the city and the collection of information called living sources, with 25 deponents, recorded and transcribed through semi-structured interviews, resulting in Volume II. The intersection of sources, with equal equity content, resulted in the preservation of institutional memory in addition to corroborating future research. The limits of this study are school dropout and graduates who have not entered higher education. As a suggestion for future research, it is recommended to prioritize a physical memorial center at ETEC DANS, in addition to specific studies with graduates.